Performance evaluation of space time trellis coded MIMO for mobile communications - Gebrehiwet Gebrekrstos Lema; Teklehaymanot Baweke Reda; Dawit Hailu; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The major enemy of wireless communication is multipath fading that highly degrades the received signal. Spatial diversity highly reduces deep fades of the wireless communication. Higher signal to noise ratio (SNR) requirement can be reduced by using space time coding. In this paper, the error performance of un-coded MIMO, different diversity combing methods, space time block codes and space time trellis codes are analyzed using different parameters including number of antennas, M-array modulations, trace criteria, rank and determinant. The simulation results have shown that the Bit Error Rate (BER) significantly reduces with increasing number of receiver antennas. However, the number of antennas that a mobile device can have is limited by its size and this is inconvenient for mobile communication. Hence, this paper suggests space time codes to mitigate multipath problems in mobile communication. So, BER performance of space time block codes scheme was evaluated by varying the number of transmitter and receiver antennas along with varying M-array PSK modulation orders. The results have shown that better BER is possible by integrating space time codes with spatial diversity. Finally, the error performance of space time trellis codes was evaluated by using trace, rank and determinant, and the simulation results depicted that better error performance is achieved using the proposed multipath reduction method.